Diverting Ileostomy Duration Is the Main Determinant of Ileostomy-Related Complications after Surgical Treatment of Rectum Cancer. (7th April 2020) - Hacim, Nadir Adnan; Akbas, Ahmet; Meric, Serhat; Altinel, Yüksel; Karabay, Onder; Yavuz, Erkan
Abstract : Background . This study aimed to investigate factors associated with the development of ileostomy complications in rectal cancer patients, including those who received neoadjuvant treatment. Methods . This retrospective trial included 133 consecutive patients who underwent surgery for rectal cancer with temporary diverting ileostomy. Patients' demographic characteristics as well as the pre- and postclosure outcomes and complications were analyzed. Results . In logistic regression analysis, longer duration of ileostomy emerged as a significant independent predictor of any complication during ileostomy. The respective odds ratios for 3–6 months and >6 months vs. <3 months of ileostomy duration were as follows: OR, 4.5 (95% CI, 1.2–16.7), p = 0.023 ; and OR, 15.2 (95% CI, 3.1–75.2), p = 0.001 . An additional stepwise model also identified hypertension as a significant predictor. In stepwise logistic regression model, adjuvant chemoradiotherapy emerged as significant independent predictor of "any ileostomy-related complication after ileostomy closure": OR, 4.5 (2.0–10.2), p < 0.001 . Conclusion . Duration of ileostomy appears to be the main determinant of ileostomy-related complications. Patients who had received neoadjuvant or adjuvant therapy had longer ileostomy duration, which may be attributed to the concerns of the surgeon or to the complications themselves.